Mainstreaming Religious Moderation through Digital Literacy in Islamic Education: A Case Study of Indonesian Boarding Schools - M. Iqbal Qomaruzzaman; Muhammad Fahmi; Abd Jalil (IJoIS: Indonesian Journal of Islamic Studies, 2026)
Religious moderation is a key principle in fostering a tolerant and inclusive character among students, especially within a multicultural society and the digital age. Although many studies have discussed religious moderation in schools, limited research has specifically examined how digital literacy is integrated into Islamic Education (PAI) to strengthen students’ critical religious understanding in boarding-based Islamic senior high schools. This study addresses that gap by exploring the integration of digital literacy and religious moderation within two Islamic educational institutions: SMA Al-Huda Tuban and SMA Aisyiyah Boarding School Malang (ABSM). Using a qualitative multi-case study approach, data were collected through interviews, classroom observations, and documentation involving teachers, principals, and students. The findings reveal that both schools integrated moderation values, such as tolerance, inclusiveness, anti-violence, and nationalism, into digital-based PAI learning. Teachers utilized digital media, including YouTube, blogs, and social media platforms, to encourage reflective and contextual learning, while students engaged in moderation-themed digital projects. The study shows that digital literacy functions not only as a technical competence but also as a critical pedagogical tool for evaluating religious information and resisting intolerant narratives online. Despite challenges related to infrastructure and teacher digital competence, the integration of digital literacy and religious moderation contributed positively to students’ critical awareness and inclusive religious attitudes. This study highlights the role of digital pedagogy in strengthening moderate Islamic education in the post-truth era.